Kepribadian Tokoh Utama Pada Kumpulan Cerpen Keluarga dan Silsilah Suka Duka Karya Ismail Basbeth : The Main Characters in the Short Story Collection Family and Genealogy: Joys and Sorrows by Ismail Basbeth - Amelia Utami Eka Putri; Sahlan Mujtaba; Een Nurhasanah (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This study aims to describe the personality structure of the main characters in the short story collection Keluarga dan Silsilah Suka Duka by Ismail Basbeth. This research is motivated by the increasing number of mental health problems among adolescents, which are often triggered by family conflict, social pressure, and unstable psychological development. Examining the personality structure of literary characters is important because it provides insight into how an individual’s personality is formed through internal conflicts, value struggles, and self-control processes. The subjects of this study consist of five selected short stories that contain themes and events closely related to adolescents’ daily lives and are suitable for use as learning materials. This study employs a descriptive qualitative method with content analysis and note-taking techniques to identify the presence of id, ego, and superego within the main characters. The results show that the short story “Televisi” contains nine personality data (four id, three ego, two superego); “Tinju Api” contains seven (three id, two ego, two superego); “Poligami” contains six (two id, two ego, two superego); “Pesugihan” contains six (three id, three ego, and no superego); and “Maryam” contains nine (three id, three ego, three superego).